The Effect of Growth Opportunities, Political Costs, and Litigation Risk on Accounting Conservatism: A Case Study on the Secondary Consumer Sector Listed on the Indonesia Stock Exchange in 2018-2021 - Aurelia Pamungkas, Amarsya; Lestari, Tri Utami (SEAN Institute, 2025)
Conservatism is an important principle for recognizing and measuring assets and profits in financial statements and is done carefully because it is in an environment of uncertainty. This study aims to determine the effect of Growth Opportunities, Litigation Risk and Political Costs on Accounting Conservatism. The population used in this study is secondary consumer sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The research data used in this study was 160 observational data. The method used in this study was panel data regression analysis and using EViews 10 software. The results of this study show that simultaneously growth opportunities, litigation risk and political costs together influence accounting conservatism. Meanwhile, partially growth opportunities have no influence on accounting conservatism. Litigation risk positively affects accounting conservatism. And, political costs have a negative influence on accounting conservatism.